Perancangan E-Voting pemilihan Kepala Desa untuk Transparansi Informasi di Kecamatan Lueng Bata Kota Banda Aceh - Susmanto Susmanto; Munawir Munawir; Erdiwansyah Erdiwansyah; Zulfan Zulfan; Didik Setiyadi (Jurnal Serambi Engineering, 2022)
The Village Government (geuchik), has a very important role in regulating and managing the interests of the community both in the village government and in the form of village head elections. Therefore, to create a clean and transparent village government in the election of the village head, in this study I will create an E-Voting program in the election of the village head. However, as time goes on and based on facts on the ground, what has been done so far, there are still many shortcomings and problems in data validation and the lack of knowledge and a high level of public emotionality in winning one candidate for village head, thus triggering conflict between residents, on the other hand the electoral system Conventionally, village heads can also be indicated as cheating. In an effort to avoid fraud in the village head election (Geuchik), an idea or idea is needed in the form of using technology based on the E-voting website and can be run using a computer or laptop device that has the E-Voting application installed so that it can be done transparently, effectively, efficient and professional that is expected in the election of the Village Head, in supporting E-Government in this study will be carried out in the Batoh Village (Gampong), Luengbata sub- district, Banda Aceh City.